2021
DOI: 10.1016/j.mtbio.2021.100153
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized droplet microarray platform enables maintenance of human induced pluripotent stem cell pluripotency

Abstract: The capacity of human induced pluripotent stem cells (hiPSCs) for indefinite self-renewal warrants their application in disease modeling, drug discovery, toxicity assays and efficacy screening. However, their poor proliferation ability, inability to adhere to surfaces without Matrigel coating and tendency to spontaneously differentiate in vitro hinder the application of hiPSCs in these fields. Here we study the ability to culture hiPSCs inside 200 ​nL droplets on the droplet microarray (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The viability was measured by a live–dead staining as described previously. [ 44 ] The viability of cells after noncontact printing was higher than that of manual seeding. This might be due to the higher volume of each spot after printing (200 nL) than the volume of manual seeding (≈80 nL) could provide more nutrient for cell growing and survival.…”
Section: Resultsmentioning
confidence: 99%
“…The viability was measured by a live–dead staining as described previously. [ 44 ] The viability of cells after noncontact printing was higher than that of manual seeding. This might be due to the higher volume of each spot after printing (200 nL) than the volume of manual seeding (≈80 nL) could provide more nutrient for cell growing and survival.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory, we have developed a "Droplet Microarray" (DMA) platform, formed by superhydrophobic-hydrophilic patterning. [36][37][38][39][40][41][42][43] Using this platform, various cell-based experiments are possible in hundreds to thousands of micro-or nanoliter cell culture reservoirs, separated by superhydrophobic borders on a single microscope glass slide. DMAs can be prepared on various types of substrates, e.g., nanostructured glass, [37] porous poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) polymer (HEMA-EDMA), [38,39] poly(thioether) dendrimers [44] etc.-having a broad range of surface topography and roughness.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43] Using this platform, various cell-based experiments are possible in hundreds to thousands of micro-or nanoliter cell culture reservoirs, separated by superhydrophobic borders on a single microscope glass slide. DMAs can be prepared on various types of substrates, e.g., nanostructured glass, [37] porous poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) polymer (HEMA-EDMA), [38,39] poly(thioether) dendrimers [44] etc.-having a broad range of surface topography and roughness. We have demonstrated that HeLa-CCL2 cells cultured on different biomaterial-coatings used for fabrication of DMA, and in droplets of as low as 9 nL volumes exhibit no drastic transcriptomic alternations in comparison to cells grown in microtiter plates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations